Thinking styles and academic achievement among Filipino students - Bernardo, Allan B. I. (Animo Repository, 2002)
The authors' objective in this study was to determine whether the precepts of R. J. Sternberg's (1988, 1997) theory of mental self-government apply to a non-Western culture. They administered R. J. Sternberg and R. K. Wagner's (1992) Thinking Styles Inventory, which is based on the theory of mental self-government, to 429 Filipino university students. The results of item analysis, scale intercorrelations, and factor analysis were consistent with the general provisions of the theory. Correlational analysis between thinking styles and grade point average showed that thinking styles are related to academic achievement. The results are explained with respect to the concepts and practices of Philippine culture and schools and discussed in relation to the developmental assumptions of the theory of mental self-government. © 2002 Taylor & Francis Group, LLC.